Types of Cannabis and Tobacco/Nicotine Co-Use and Associated Outcomes in Young Adulthood - Tucker, Joan S. (Psychol Addict Behav, 2019)
OBJECTIVES: Cannabis and tobacco/nicotine use are highly comorbid. Given expanding access to cannabis through legalization for recreational use, it is important to understand how patterns of cannabis and tobacco/nicotine co-use are associated with young adult outcomes. METHODS: A predominantly California-based sample of 2,429 young adults (mean age=20.7) completed an online survey. Based on past-year reports of cannabis and tobacco/nicotine use, we defined five mutually exclusive groups: (1) single-product use; (2) concurrent use only (using both products, but only on separate occasions); (3) sequential use only (using both products on the same occasion, one right after the other, but not mixing them together); co-administration only (using both products on the same occasion by mixing them in the same delivery device); and both sequential use and co-administration. We examined group differences in use patterns, dependence, consequences of marijuana use, and psychosocial functioning. RESULTS: Fifty percent of respondents reported cannabis use, 43% tobacco/nicotine use, and 37% co-use of both substances. The most prevalent method of co-use involved smoking combustible products. Overall, individuals who co-used reported heavier marijuana and tobacco/nicotine use and greater problematic behaviors than those who did not co-use. However, differences in physical, mental and social functioning varied by co-use category, with sequential use (especially among those that also engaged in co-administration) typically associated with worse functioning overall compared to using each substance separately. CONCLUSIONS: Findings illuminate both prevalence and risks associated with co-use of cannabis and tobacco/nicotine products, and can inform policies for states considering regulation of cannabis and tobacco/nicotine products.